Patterns and pathways of lead contamination in mottled ducks (Anas fulvigula) and their habitat - Kearns, Brian Vance (Kansas State University, 2015)
Mottled ducks (Anas fulvigula) are dabbling waterfowl species native to coastal wetlands of the Gulf of Mexico of the United States and Mexico. Although closely related to common waterfowl species such as the mallard (A. platyrhynchos) and American black duck (A. rubripes), the mottled duck exhibits unique behavior, mainly in its life history as a non-migratory species. As such, because of population declines caused by predation, habitat destruction, and environmental contaminants, this species requires specialized conservation concerns and species-specific management to protect population numbers. The goal of this study was to assess ongoing effect of observed lead (Pb) contamination and exposure issues in mottled ducks and their habitats, which I achieved by conducting assessments that will provide managers habitat and organism level metrics to detect and mitigate lead in mottled ducks and their environments. My field study was conducted at the Texas Chenier Plain National Wildlife Refuge Complex (TCPC), which was the area of greatest mottled duck density on the Texas Coast. I first created a body condition index to provide managers a tool to monitor population health, and a proxy for lead exposure and avian health without destructively sampling individuals. I then used presence-only maximum entropy (MaxENT) and multivariate statistical modeling procedures in conjunction with mottled duck movement data to elucidate sets of habitat conditions that were conducive to predicting the occurrence of mottled ducks and environmental lead “hot spots”. MaxENT analyses suggested that lead in the top portion of the soil column is similarly related to all environmental variables considered, may be increasingly available after large-scale environmental disturbances. Lack of variation in coarse-scale habitat use between breeding and non-breeding seasons may further point to a food-based exposure pathway for lead as mottled ducks switch from an invertebrate to plant diet, either as a result of changing age classes or normal adult phenology, during the period of increased lead exposure. Using stable isotope ratio analysis, I then tested environmental samples of soil and vegetation as well as mottled duck blood to determine isotopic signatures that were consistent with particular sources of lead deposition (e.g., lead shot pellets, leaded fossil fuel combustion, industrial effluents). Comparisons suggested a great deal of similarity to lead shot reference values in vegetation and blood samples, especially in blood samples with higher concentrations of lead present. Last, I conducted a formal Ecological Risk Assessment (ERA) procedure to quantify the risk to mottled ducks from lead exposure in their current habitat and direct managers towards effective mitigation and habitat management strategies to reduce exposure in the future. One scenario suggested that mottled ducks were at greatest risk from eating an invertebrate-based diet, but lead content values at the TCPC suggest that a plant-based diet may provide a higher lead exposure risk for mottled ducks, depending on true levels of bioavailability in environmental media. Overall, I determined that mottled ducks experience greatest lead exposure risk from lead shot pellets on the TCPC or in nearby habitat, while potentially also experiencing low levels of exposure from several other sources. Additionally, management efforts that focus on plants that do not provide food resources for mottled ducks as a potential environmental sink for lead contamination, such as phytoremediation, may prove effective in reducing the overall lead load from historical activities that likely deposited much of the lead in this ecosystem.
Keywords: Waterfowl; Lead; Body condition; Species distribution; Ecological risk assessment; Stable isotope analysis; Biology (0306); Wildlife Conservation (0284); Wildlife Management (0286)